(untitled) (UNED Research Journal, 2021)
Introduction: Knowledge about the taxonomic composition of the Costa Rican freshwater fish fauna has changed substantially in the last two decades. Not only due to the addition of new species and supra-specific taxa, but also due to rearrangements and taxonomic changes at the different hierarchical levels. The available taxonomic keys were published more than 20 years ago and are outdated. Objective: To provide up-to-date information, in a friendly language, for the identification of all Costa Rican families of continental and insular fishes. Methods: We used the literature, museum collections and recently collected specimens to update a 2013 family list. Results: The key covers 53 families. The illustrated dichotomous key has is based on external characters that are relatively “easy” to identify. We also include information about species composition, general distribution and habitat use. Conclusion: This key allows the identification of 274 fish species to family level, as a basis for further identification.